Pengaruh Influencer Marketing dan Pemasaran Digital Era Modern terhadap Loyalitas Konsumen Produk Emina (Studi Kasus Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Jember) - Sari, Serli Anggita; Setianingsih, Wahyu Eko; Rusdiyanto, Rusdiyanto (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this research is to analyze the influence of influencer marketing and digital marketing on consumer loyalty for Emina products. This research is quantitative research. The population in this study was 1423 students at Muhammadiyah University of Jember from the 2019 to 2022 academic year who used Emina products. Researchers used sampling techniques using non-probability sampling techniques with purposive sampling. Determining the number of samples in this study used the Slovin formula, so based on the Slovin formula the number of research samples was 312 students. The analytical method used is descriptive and quantitative statistical analysis with SPSS application tools, version 21. The tests used are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, t test and coefficient of determination test. The results of this research state that these two variables, namely influencer marketing and digital marketing, have a significant effect on consumer loyalty for Emina products. The coefficient of determination value for this research was 73.1%. Keywords : Digital Marketing, Influencer marketing, Product Consumer Loyalty